Condition of Coral Reefs in Kiya Village - Syahnul S. Titaheluw; Umar Tangke; Mahmud Hasan; Fathnun Tan (BIOSAINSTEK, 2025)
This study aims to analyze the condition of the coral reef ecosystem in the waters of Kiya Village using the Line Intercept Transect (LIT) method along a 25-meter transect at a depth of 5 meters. The observation results show that the percentage of live coral cover is 29%, which is classified as moderate according to the criteria of Gomez & Yap (1988). The composition of other substrates consists of Dead Scleractinia 12.8%, algae 12.6%, other fauna 22.4%, and abiotic components 23.2%. The relatively high Dead Scleractinia value indicates ecosystem degradation, which is suspected to be influenced by natural and anthropogenic factors, including the potential impact of nickel mining activities in the Gemaf area. The significant proportion of algae and abiotic components has the potential to inhibit coral regeneration and trigger shifts in the benthic community. However, the moderate category for live coral cover indicates the potential for recovery if ecosystem-based management, control of pollution sources, and community involvement are implemented. The results of this study are expected to serve as a basis for conservation and sustainable management efforts for coral reefs in Kiya Village.